Controladoria como suporte à estratégia da empresa: estudo multicaso em empresas de transportes - Nunes, Adão Alberto Blanco (Universidade do Vale do Rio dos Sinos, 2014)
This study aims to identify which controllership practices can support strategic decisions in transport enterprises. To attend this objective, was developed a multiple case study on four transportation companies established at the metropolitan region of Porto Alegre/RS. The participating companies are the specialized on road transportation load and they have consolidated brand in the market. The interviews and the fill in questionnaire occurred from April till June, 2014.To collect the information, was elaborated a structured schedule of interview with closed answers, divided into three sections. In section 1, was elaborated a questionnaire, holding the main practices of controller validate by specialists. In section 2, was elaborated a questionnaire with the objective to identify what’s the participation of the controller on the company strategy. In section 3, were listed the main strategic decision used by companies. As practices of controller used by the transportation companies, we noticed that among the 27 practices of controller presented, 16 are used by at least one of the companies, while 11 of them are not used by any of the researched companies. As the adherence of the controller practices by the companies of transportation, we notice that the company 3 has the major participation with 51,9% of the practices, and that the company 1 has the fewer participation with 18,5% of utilization from validate practices. Analyzing the utilization of the strategic decisions listed on literature, we noticed that 75,4% from strategic decisions are used for at least one of the researched companies, while 24,6% of the decisions are not indentified in any one of the companies. To verify the similarity index among companies, it was used the Jaccard similarity index, on which we notice that similarity really exists, seeing that, in comparison from practices of controller used among companies, 83% of comparisons presented similarity superior to 70%. In comparison of strategic decisions, 67% of the comparisons also presented similarity superior to 70%. Besides, the results showed that 7,4% from practices of controller are considered decisive or very important for 100% of the companies, and that 14,8% of the practices are considerate decisive or very important for 75% of the companies. The results obtained from the collected data in the analyses showed that the practices of controller can give support for the formulation of strategic decisions of the company.
Keywords: Práticas de controladoria; Decisão estratégica; Empresa de transportes; Transporte de carga; Practices of controller; Strategic decisions; Transportation company; Load transportation; ACCNPQ::Ciências Sociais Aplicadas::Ciências Contábeis